2017
DOI: 10.1186/s12971-017-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and panic disorders in chronic obstructive pulmonary disease patients: correlations with tobacco use, disease severity and quality of life

Abstract: BackgroundThe objective of this study is to assess anxiety, depression and panic disorders among patients diagnosed with COPD and to investigate their correlation with disease severity, quality of life as well as tobacco use.MethodsAn observational study was performed between January and September 2014 among 60 patients diagnosed with COPD. COPD staging according to GOLD criteria, while anxiety and depression were assessed using Hospital Anxiety and Depression Scale and panic attacks were evaluated based on IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
8
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
7
8
1
5
Order By: Relevance
“…Workers with COPD at intermediate or high risk for substance use and abuse were no more likely to report mental or physical distress and limited activity due to poor health compared to those at low risk. This result is supported by Pascal et al [ 57 ] who concluded that mental conditions, specifically anxiety, depression and panic disorders, were constant characteristics of COPD patients, regardless of their current tobacco use. However, consistent with prior research [ 27 ], workers with COPD who were at high risk for multiple comorbidities were more likely to report physical distress, mental distress, and activity limitation due to poor health as compared to those at low risk for comorbidities.…”
Section: Discussionsupporting
confidence: 69%
“…Workers with COPD at intermediate or high risk for substance use and abuse were no more likely to report mental or physical distress and limited activity due to poor health compared to those at low risk. This result is supported by Pascal et al [ 57 ] who concluded that mental conditions, specifically anxiety, depression and panic disorders, were constant characteristics of COPD patients, regardless of their current tobacco use. However, consistent with prior research [ 27 ], workers with COPD who were at high risk for multiple comorbidities were more likely to report physical distress, mental distress, and activity limitation due to poor health as compared to those at low risk for comorbidities.…”
Section: Discussionsupporting
confidence: 69%
“…In a study by Lim et al (2017), the high-symptom group with a higher cluster-analysis score had poorer QoL than the low-symptom group with a lower cluster-analysis score. According to the theory of unpleasant symptoms, multiple symptoms or symptom clusters may exert a synergistic effect on health outcomes (Dodd et al, 2001; Lenz et al, 1997; Pascal, Trofor, Lotrean, Filipeanu, & Trofor, 2017). This study examined the relationship between symptom clusters and HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is important for several reasons. First, patients with CVD, COPD or diabetes who smoke are priority populations for tobacco treatment 1,30 , despite this, low rates of intervention are reported in health care settings. Second, the majority of health care providers, including specialists working with highrisk populations, have not been trained in evidencebased tobacco treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%